Assessing Subsequent-Year Performance of Morningstar Award-Winning Large-Cap Equity Funds in Thailand - Wissawapaisal, Komwut (วารสารนวัตกรรมธุรกิจ การจัดการ และสังคมศาสตร์, 2024)
This research objective was to evaluate the performance of the Morningstar’s award-winning large-cap equity mutual funds in Thailand over a 10-year period. Annual returns were compared to the SET50 Total Return Index (SET50 TRI), a benchmark for large-cap equity funds. Findings showed that, despite receiving the awards, the funds did not outperform the benchmark in the first, second, and third years. The probabilities of outperforming were 36%, 30%, and 11% respectively. This highlights the challenges faced by these funds in sustaining exceptional performance over time. The study contributes to understanding the relationship between Morningstar Awards, subsequent fund performance, and benchmark comparisons.